Tao controls epithelial morphogenesis by promoting Fasciclin 2 endocytosis - Gomez, Juan Manuel; Wang, Ying; Riechmann, Veit (The journal of cell biology, 2012)
Regulation of epithelial cell shape, for example, changes in relative sizes of apical, basal, and lateral membranes, is a key mechanism driving morphogenesis. However, it is unclear how epithelial cells control the size of their membranes. In the epithelium of the Drosophila melanogaster ovary, cuboidal precursor cells transform into a squamous epithelium through a process that involves lateral membrane shortening coupled to apical membrane extension. In this paper, we report a mutation in the gene Tao, which resulted in the loss of this cuboidal to squamous transition. We show that the inability of Tao mutant cells to shorten their membranes was caused by the accumulation of the cell adhesion molecule Fasciclin 2, the Drosophila N-CAM (neural cell adhesion molecule) homologue. Fasciclin 2 accumulation at the lateral membrane of Tao mutant cells prevented membrane shrinking and thereby inhibited morphogenesis. In wild-type cells, Tao initiated morphogenesis by promoting Fasciclin 2 endocytosis at the lateral membrane. Thus, we identify here a mechanism controlling the morphogenesis of a squamous epithelium.